Policies to decrease inbreeding in the Cinta Senese pig - Gandini G.; Orlandini P.; Franci O.; Campodoni G. (Tradition and innovation in Mediterranean pig production, 2000)
Inbreeding in the Cinta Senese pig rapidly increased during the last 15 years to the current level of 0.172. Several observations suggest severe inbreeding depression on fertility and survival to weaning. This paper discusses a breeding scheme to reduce inbreeding in the very short term. Management criteria include: optimization of population effective size, minimum kinship selection of boars and sows and minimum inbreeding mating. A mean inbreeding of 0.043 is expected in the next generation, which is 67 per cent lower than under the hypothesis of no management.
4. International Symposium on Mediterranean Pig, 1998/11/26-28, Evora (Portugal)